10-3(m-2)=7

Simple and best practice solution for 10-3(m-2)=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10-3(m-2)=7 equation:


10-3(m-2)=7

We simplify the equation to the form, which is simple to understand
10-3(m-2)=7

Reorder the terms in parentheses
10+(-3m+6)=7

Remove unnecessary parentheses
+10-3m+6=+7

We move all terms containing m to the left and all other terms to the right.
-3m=+7-10-6

We simplify left and right side of the equation.
-3m=-9

We divide both sides of the equation by -3 to get m.
m=3

See similar equations:

| 4x-13=2(3-x) | | 5w+27+4w=9 | | 8-2t=14+t | | 2(2y-1)+y=5(y+3) | | -9x+5(-3x-4)=-42-2x | | 40+40*0+1= | | 2x+7(3x-4)=-2-3x | | -8x^2+24x-18= | | -16+x=450 | | 5x^2+50x=0 | | -5x+x=-16 | | 120x^2-272x+120=0 | | 5*5*5*5= | | 2t^2+2t=3 | | 10-3(-8-2)= | | 120x^2-272x+102=0 | | 10x-0.375-4x=6x | | 2+x=16-6x | | 30a=2a-8 | | 976x-x^2=213.495 | | 1/14=27/7*1/30 | | 10x-2y=5 | | -2x^2+17x-8=0 | | 6x-2y=1 | | -99=33y | | 8j-4k=4 | | 5(k-2)-6=5k-(4k-3) | | 3j+4k=23.5 | | 11f+10g=25 | | Y=150x+800 | | 22=-2+3s | | -2-19= |

Equations solver categories